Wartime rape as strategic weapon in selected contemporary plays written in English - Salih, Elaff Ganim (2017)
Wartime rape as a form of sexual violence is not a new phenomenon. It is as old as war itself. Misconceptions and mischaracterization of wartime rape as a natural byproduct of war, spoils of war and a biological need have reinforced its acceptance as a natural aspect of war. Moreover, marginalizing wartime rape as a feminist issue expels it from being weaponized as a political strategy. Also, there is a gendered misconception of rape casting man and woman to certain sexual patterns that man is the ultimate perpetrator of rape whereas woman is the sole victim due to the myth of man’s invulnerability to rape. Furthermore, the exclusion of man from being a victim of wartime rape and justifying it as a homosexual act is another misconception. However, with the changing face of contemporary wars, the use of traditional weapons becomes unsatisfactory. Thus, the current study argues that wartime rape is adopted as an effective tactic and weapon of war used massively in contemporary wars to advance certain strategic military and political goals. Therefore, the first objective of this study is to examine the strategic function of wartime rape in the selected dramatic texts in light of the Strategic Rape Theory to refute the misconception that wartime rape is a consequence and to examine its weaponization at war. The second objective is to explore women rape by men away from the definitions of misogyny and patriarchy in light of the Strategic Rape Theory and the Social Constructionist Concept. The third objective is to investigate the acts of wartime rape committed in the selected plays to refute the misconception that rape is gender-specific depending on the Social Constructionist Concept and to investigate the mechanism of rape’s victimization and perpetration. The study depends on Jonathan Gottschall’s Strategic Rape Theory (2004) and Inger Skjelsbaek’s Social Constructionist Concept (2001) in the analysis of the selected plays. The significance of the study lies in challenging these misconceptions and setting strategizing wartime rape’s conception instead. The study offers a complete explanatory framework that recognizes the weaponization of rape at warfare as a violent political act inserting men and women as victims and perpetrators rather than as an individual act mobilized by biological and social powers. Sarah Kane’s Blasted (1995), Colleen Wagner’s The Monument (1995), Lynn Nottage’s Ruined (2007), and Judith Thompson’s Palace of the End (2007) are selected for the study. They are selected because they show how sex is weaponized and militarized in the contemporary war by depicting new patterns of rape. The selection of playwrights of different nationalities and cultures is justified due to the universality of the strategic aspect of wartime rape. The study concludes that war rape is not a violent expression of sexual desire but a sexual expression of violence to terrorize, eradicate, and humiliate a whole nation for strategic outcomes according to certain political agenda. Moreover, it concludes the existence of a relationship between rape and the strategic choices of the military and political leadership.